Centaurea dimorpha Viv. (Asteraceae) growing in Algeria extracts as a promising natural cosmetic active ingredient: Broad-spectrum photoprotection and antioxidant efficacy - Azzouzi, Salima; Lefahal, Mostefa; Louaar, Souheila; Makhloufi, El-Hani; Medjroubi, Kamel; Akkal, Salah (Future Science, 2025)
Recently, plants have been considered as a valuable natural source of cosmetic active ingredientsowing to their sustainability and weak toxicity. Thus, this study was conducted to investigate the cosmetic efficacy of Centaurea dimorpha Viv (Asteraceae), an endemic species of North Africa, as a promising natural cosmetic active ingredient. In the present study, Ethyl acetate and Butanolic extracts obtained from powdered Centaurea dimorpha aerial parts were investigated for their phenolic and flavonoid contents, which were evaluatedvia Folin-ciocalteu reagent and aluminium chloride methods, the in vitro antioxidant potential was evaluated by DPPH radical scavenging,phosphomolybdenum and phenanthroline assays, the UVB and broad spectrum protective efficacy was spectrophotometrically assessed by measuring SPF, UVA/UVB ratio and critical wavelength (CW) indices. The highest levels of TPC and TFCwere recorded by the ethyl-acetate extract (119.20 ± 0.32 µg GAE mg-1, 50.65 ± 0.43 µg QEmg-1, respectively). Similarly, this extract displayed a significant antioxidant effect, particularly in the phenanthroline assay (152.63 ± 0.49 µg AAEmg-1). Ethyl acetate extract also showed UVB and broad-spectrum (UVB-UVA) protective efficacy (SPF=12.30 ± 0.001, UVA/UVB ratio=0.63 ± 0.001, λc= 371). The results obtained show the possibility to use Ethyl acetate extract as a promising active ingredient for sunscreen formulations.